Integrating Agroforestry and Aquaculture: Effects of Moringa oleifera Leaf Extract on Growth Performance of White Snapper (Lates calcarifer) - Lidya Ika Mefida; Nuning Nurcahyani; Enur Azizah; Sutyarso (Forest and Nature, 2026)
The integration of agroforestry and aquaculture systems has been increasingly explored to improve resource utilization and support sustainable food production. This study evaluates the potential of moringa (Moringa oleifera), a multifunctional agroforestry species, as a feed supplement for white snapper (Lates calcarifer). An experimental study was conducted using a completely randomized design with four dietary treatments: 0% (control), 2.5%, 5%, and 7.5% moringa leaf extract supplementation, each with three replicates, over a 28-day rearing period. Growth performance, including absolute length and weight gain, specific growth rate (SGR), survival rate (SR), and feed conversion ratio (FCR), was measured. The results showed that fish receiving moringa-supplemented feed generally exhibited higher growth values compared to the control. The highest average weight gain was observed in the 5% treatment (9.28 g), while the highest SGR was recorded in the 2.5% treatment (4.79% day⁻¹). Survival rates in all supplemented treatments reached 100%, compared to 90% in the control group, indicating favorable culture conditions and no adverse effects of supplementation. FCR values across treatments remained above 2, suggesting relatively low feed utilization efficiency. This may be related to the carnivorous feeding characteristics of white snapper, which can limit the effective use of plant-based feed components. Water quality parameters, including temperature, pH, and dissolved oxygen, remained within acceptable ranges throughout the study. This study provides empirical evidence supporting the integration of agroforestry biomass into aquaculture feed systems. The use of moringa as a locally available, renewable resource contributes to circular nutrient flows, reduces reliance on imported feed ingredients, and promotes environmentally sustainable aquaculture practices. These findings advance the development of integrated agroforestry–aquaculture systems as resilient and eco-efficient production models in tropical regions.